Deixis in Hate Speech in the 2024 Presidential Election Campaign on Social Media X: A Cyber Pragmatic Study - Herpindo Herpindo; Astuty Astuty; Muhammad Khoirul Huda; Ahmad Shohibul Ghoni; Fandi Aulia Rahman (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2026)
The purpose of this study is to analyze the systematic use of deictic expressions in hate speech targeting presidential candidates on platform X during Indonesia's 2024 election campaign period. This research seeks to understand how linguistic mechanisms, particularly deixis, function as strategic tools for constructing power relationships, facilitating dehumanization, and undermining democratic discourse in digital political communication. The study employs a descriptive qualitative design using a cyber-pragmatic approach to analyze hate speech on social media platform X during Indonesia's 2024 presidential election campaign, with data collected through observation and screenshot documentation of linguistic phenomena containing deictic expressions, followed by analysis using note-taking techniques to identify hate speech components and their linguistic patterns. Based on the analysis of 45 hate speech incidents targeting Indonesian presidential candidates on social media platform X during the 2024 election campaign, the study reveals that Prabowo Subianto-Gibran Rakabuming Raka received the highest targeting (44.4%), followed by Anies Baswedan-Muhaimin Iskandar (37.8%), with insults and profanity comprising the dominant category (34.8%) of hate speech. The deictic analysis demonstrates that social deixis shows the strongest correlation with ethnic attacks and stereotyping, while systematic dehumanizing language patterns vary distinctly across candidate pairs, reflecting deep political polarization facilitated through strategic linguistic positioning mechanisms. The systematic distribution of hate speech through deictic linguistic strategies during Indonesia's 2024 presidential election campaign, which disproportionately targeted certain candidates through social deixis-facilitated ethnic attacks and dehumanization, necessitates the immediate implementation of AI-powered pattern recognition systems, real-time monitoring protocols, and comprehensive digital literacy programs to protect democratic discourse integrity and safeguard future electoral processes.